The conscience of the game : baseball's commissioners from Landis to Selig - Moffi, Larry (University of Nebraska Press, 2006)
Baseball once evoked all that was wholesome and sound in the world of sports: team spirit and fair play. But recently, the national pastime has exemplified much of what is wrong with the American sporting scene, from steroid abuse and conflicts of interest to antitrust maneuvers and gambling scandals. In one fan's journey across the often unforgiving and frequently mysterious terrain known as "the best interests of the game," this book examines the office of the commissioner of baseball and offers a fair and original assessment of how - or whether - the commissioner truly acts as the conscience of America's game. Written in a style at once conversational and provocative, and informed by the history of the game, the office, and the nine men who have held it, "The Conscience of the Game" looks at the office of baseball commissioner from its beginnings in 1920 to the present. Throughout, Larry Moffi addresses the fundamental issues of the office's relevance and effectiveness today.; He responds to a critical question: With the office a mere arm of the corporation that operates major league baseball and the present commissioner vilified as no predecessor has been, what can be done now to return the office to the game - and to the fans - it purports to serve? Larry Moffi is the author of five previous books, including "Crossing the Line: Black Major Leaguers, 1947-1959", and "This Side of Cooperstown: An Oral History of Major League Baseball in the 1950s."